Advanced brain ageing in Parkinson's disease is related to disease duration and individual impairment. Issue 3 (23rd August 2021) - Eickhoff, Claudia R; Hoffstaedter, Felix; Caspers, Julian; Reetz, Kathrin; Mathys, Christian; Dogan, Imis; Amunts, Katrin; Schnitzler, Alfons; Eickhoff, Simon B
Abstract: Machine learning can reliably predict individual age from MRI data, revealing that patients with neurodegenerative disorders show an elevated biological age. A surprising gap in the literature, however, pertains to Parkinson's disease. Here, we evaluate brain age in two cohorts of Parkinson's patients and investigated the relationship between individual brain age and clinical characteristics. We assessed 372 patients with idiopathic Parkinson's disease, newly diagnosed cases from the Parkinson's Progression Marker Initiative database and a more chronic local sample, as well as age- and sex-matched healthy controls. Following morphometric preprocessing and atlas-based compression, individual brain age was predicted using a multivariate machine learning model trained on an independent, multi-site reference sample. Across cohorts, healthy controls were well predicted with a mean error of 4.4 years. In turn, Parkinson's patients showed a significant (controlling for age, gender and site) increase in brain age of ∼3 years. While this effect was already present in the newly diagnosed sample, advanced biological age was significantly related to disease duration as well as worse cognitive and motor impairment. While biological age is increased in patients with Parkinson's disease, the effect is at the lower end of what is found for other neurological and psychiatric disorders. We argue that this may reflect a heterochronicity between forebrain atrophy and small but behaviourally salient midbrain pathology. Finally, we point to the need to disentangle physiological ageing trajectories, lifestyle effects and core pathological changes. Abstract : Eickhoff et al., analysed 'brain age', in two samples of Parkinson's patients (de-novo and chronic). They found a significant increase in biological compared to chronological age of ∼3 years, which was already present in de-novo patients and significantly related to disease duration as well as worse cognitive and motor impairment. Graphical Abstract: